2017
DOI: 10.1063/1.4995438
|View full text |Cite
|
Sign up to set email alerts
|

Using strain to control molecule chemisorption on silicene

Abstract: The strain dependence of benzene chemisorption on a silicene freestanding layer has been studied by means of density functional theory calculations. It appears that the molecule, which is adsorbed via a [4+2] pseudo-cycloaddition on the substrate, is more stable when adsorbed on strained than on unstrained silicene since the adsorption energy increases (in absolute value) with tensile or compressive strain. These results, which were not easily predictable, are interpreted in terms of strain-induced reinforceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…To mimic the in-plane biaxial strain imposed on the HCHO@β 12 -borophene/SnO 2 system, the lattices are fixed during the structural optimization. In this study, the in-plane biaxial strain on the HCHO@β 12 -borophene/SnO 2 system was applied by equally changing the a and b lattice constants while relaxing the structure along the out-of-plane lattice parameter c , and the biaxial strain was defined by where ε, a , and a 0 are the in-plane biaxial strain and the optimized lattice constants of the unstrained and strained structures, respectively . The value of ε changing from −6 to 6% predicted that the HCHO@β 12 -borophene/SnO 2 system imposed biaxial strains from pressure to tension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To mimic the in-plane biaxial strain imposed on the HCHO@β 12 -borophene/SnO 2 system, the lattices are fixed during the structural optimization. In this study, the in-plane biaxial strain on the HCHO@β 12 -borophene/SnO 2 system was applied by equally changing the a and b lattice constants while relaxing the structure along the out-of-plane lattice parameter c , and the biaxial strain was defined by where ε, a , and a 0 are the in-plane biaxial strain and the optimized lattice constants of the unstrained and strained structures, respectively . The value of ε changing from −6 to 6% predicted that the HCHO@β 12 -borophene/SnO 2 system imposed biaxial strains from pressure to tension.…”
Section: Resultsmentioning
confidence: 99%
“…where ε, a, and a 0 are the in-plane biaxial strain and the optimized lattice constants of the unstrained and strained structures, respectively. 89 The value of ε changing from −6 to 6% predicted that the HCHO@β 12 -borophene/SnO 2 system imposed biaxial strains from pressure to tension. The strain range of −6% ≤ ε ≤ 6% used in this study was relatively feasible in an experiment.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…It is known that applying a tensile or compressive strain is an alternative way to alter the electronic distribution and chemical potential of silicene. , In addition, the barrier of the dissociation of molecular hydrogen on silicene can be greatly reduced by applying strain on the substrate as discussed above . Therefore, strain field is considered here to investigate the possibility of lowering the dissociation energy barrier of water molecules on silicene.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, external stimulations should be applied to depress the dissociation barrier for H 2 O molecules on silicene. Strain field is effective to change the surface activity of low-dimensional materials. It is reported that strain can enhance the binding energy and charge transfer between water and the substrate on an in-plane graphene/silicene heterostructure . Our recent work also reported that the dissociative barrier of H 2 molecules on silicene can be significantly depressed in the presence of strains .…”
Section: Introductionmentioning
confidence: 81%
“…Adsorption energies are generally assumed to vary linearly with strain. ,, We noted that there are often nonlinear relations between adsorption energy and strain. ,, BEP and TSS relations are closely related to adsorption energies. Will BEP and TSS relations also be nonlinear under strain?…”
mentioning
confidence: 99%